Interactive effects of fishing effort reduction and climate change in a central Mediterranean fishing area: Insights from bio-economic indices derived from a dynamic food-web model - Agnetta, Davide; Badalamenti, Fabio; Colloca, Francesco; Cossarini, Gianpiero; Fiorentino, Fabio; Garofalo, Germana; Patti, Bernardo; Pipitone, Carlo; Russo, Tommaso; Solidoro, Cosimo; Libralato, Simone (Frontiers in Marine Science, 2022)
Disentangling the effects of mixed fisheries and climate change across entire food-webs requires a description of ecosystems using tools that can quantify interactive effects as well as bio-economic aspects. A calibrated dynamic model for the Sicily Channel food web, made up of 72 functional groups and including 13 fleet segments, was developed. A temporal simulation until 2050 was conducted to evaluate the bio-economic interactive effects of the reduction of bottom trawling fishing effort by exploring different scenarios that combine fishery and climate change. Our results indicate that direct and indirect effects produce a net increase in biomass of many functional groups with immediate decline of trawlers’ catches and economic incomes, followed by a long term increase mainly due to biomass rebuilding of commercial species which lasts 5-10 years after fishing reduction. Synergistic and antagonistic effects caused by changes in the fishing effort and in climate characterize a specific functional group’s response in biomass which, in turn, modulate also the catch and income of the other fleets, and especially of those sharing target resources. However, trawler’s intra-fleet competition is higher than the others fleet effects. In the medium term, the effects of fishing effort reduction are higher than those of climate change and seem to make exploitation of marine resources more sustainable over time and fishery processes more efficient by improving ecosystem health.